Pengaruh Pelatihan, Motivasi Berwirausaha, dan Jiwa Kewirausahaan terhadap Kinerja Usaha pada Pelaku Usaha Industri Kreatif Rotan di Pekanbaru - Anugrah Bima; Susi Hendriani; Yulia Efni (Program Studi Manajemen FEBM UMRAH, 2022)
This study aims to determine the effect of training, entrepreneurial motives, and entrepreneurial spirit on the performance of business actors in the creative rattan industry in Pekanbaru. The population in this study included rattan business actors in Pekanbaru City who found 40 business actors. Primary data were collected using a questionnaire as an instrument to prove the results of the study, to test the hypothesis in this study using multiple linear regression with the help of the SPSS program. The sampling technique that has been selected is the census method (40 rattan business actors in Pekanbaru).The results showed that: 1) training had a significant effect on business performance of the rattan creative industry in Pekanbaru, 2) entrepreneurial motives had no significant effect on business performance of business actors in the creative rattan industry in Pekanbaru, 3) entrepreneur spirit had a significant effect on business performance of business actors. rattan creative industry in Pekanbaru, 4) training, entrepreneurial motives, and entrepreneurial spirit together have a significant effect on the performance of business actors in the creative rattan industry in Pekanbaru.